Self‐Healable Solid Polymeric Electrolytes for Stable and Flexible Lithium Metal Batteries. (30th October 2019) - Wu, Na; Shi, Ya‐Ru; Lang, Shuang‐Yan; Zhou, Jin‐Ming; Liang, Jia‐Yan; Wang, Wei; Tan, Shuang‐Jie; Yin, Ya‐Xia; Wen, Rui; Guo, Yu‐Guo
Abstract: The key issue holding back the application of solid polymeric electrolytes in high‐energy density lithium metal batteries is the contradictory requirements of high ion conductivity and mechanical stability. In this work, self‐healable solid polymeric electrolytes (SHSPEs) with rigid‐flexible backbones and high ion conductivity are synthesized by a facile condensation polymerization approach. The all‐solid Li metal full batteries based on the SHSPEs possess freely bending flexibility and stable cycling performance as a result of the more disciplined metal Li plating/stripping, which have great implications as long‐lifespan energy sources compatible with other wearable devices. Abstract : Fest, aber flexibel : Ein selbstheilender, fester Polymerelektrolyt (mit einer raschen Selbstheilung binnen 60 s nach einem tiefen Schnitt mit einer Klinge) verleiht festen Li‐Metallbatterien freie Biegbarkeit und eine überlegene Zyklenstabilität, wie der geringe Kapazitätsabfall von 0.1 % pro Zyklus über 100 Zyklen demonstriert.